Antioxidant status in hypertensive disorders of pregnancy - Jasmina Ivanišević; Daniela Ardalić; Gorica Banjac; Jelena Janać; Petar Cabunac; Jelena Vekić; Aleksandra Zeljković; Vesna Spasojević- Kalimanovska; Nataša Karadžov Orlić; Vesna Mandić Marković; Željko Miković; Aleksandra Stefanović (Taylor & Francis Group, 2022)
Objective Pregnancy can be associated with maternal hypertension leading to possible complications in pregnancy outcome. Antioxidant status may be proned to changes during pregnancy with hypertension. The aim of our study was to estimate antioxidant status through high-risk pregnancies. Methods Seventy-nine pregnant women with high-risk for preeclampsia development were included and 46 of them developed some hypertensive disorder in pregnancy. Superoxide-dismutase (SOD) and paraoxonase 1 (PON1) activities and relative proportion of PON1 activiity on different HDL subclasses were determined in 1st, 2nd, and 3rd trimester and prior to delivery. Results SOD activity was significantly lower in 2nd and 3rd trimesters when compared to 1st trimester (P˂0.001) whereas PON1 activity was significantly higher in 3rd than in 1st trimester (P˂0.05) in group of hypertensive women. This group had significantly higher SOD and PON1 activities and relative proportion of PON1 on HDL3c subclasses in the 1st trimester, significantly increased PON1 in the 3rd trimester and prior to delivery and significantly higher PON1 activity on HDL3c subclasses (P˂0.05) than nonhypertensive group. In 1st trimester and prior to delivery, total PON1 activity and relative proportion of PON1 on HDL3c subclasses exhibited significant ability to mark out hypertension in pregnancy (P˂0.05). Conclusions SOD activity decreased whereas total PON1 activity increased during pregnancy with hypertension. Pregnant women with hypertension had higher activities of PON1 and SOD and relative proportion of PON1 on HDL3c subclasses than nonhypertensive ones. PON1 activity and relative proportion of PON1 on HDL3c subclasses exhibited significant association with hypertension in pregnancy.